Sedimentology of black shale in turbidite at Semanggol Formation - Huang, K.L. (European Association of Geoscientists and Engineers, EAGE, 2017)
Our scope of investigation is to investigate the following aspects: (1) The restricted depositional environment of black shale in an oxidising depositional environment of turbidite; and (2) The possibility of terrigenous-derived organic matter to transport from continental shelf to the inner or outer fan. A detailed facies analysis of the Semanggol Formation was carried out in three sections in the Gunung Semanggol, Baling and Nami areas to understand the occurrence and geology of black shale in turbidite. The Semanggol Formation comprises of four facies types: conglomerate, sandstone, rhythmically bedded sandstone and mudstone with mass transport deposit and black shale. The depositional process is high- to low-density turbidity current, followed by sandy and muddy debris flows and suspension fallout. Black shale of Semanggol Formation was deposited in an outer fan environment due to deposition of turbidite sheets with typical Bouma structure. The chemical equilibration with ambient water under oxidizing condition produces association of minerals that separate the oxygen depleted suspensates at the bottom of black shale beds. The type of organic matter in black shale is terrigenousderived because of the microbial degradation that specifically affects the marine-derived organic matter, leaving behind terrigenous-derived organic matter in the black shale.